Mount Pele, an ecoclimatic gradient generator - Joseph, Philippe (Acta Geographica Debrecina Landscape & Environment series, 2013)
Generally, mountains determine the characteristics of particular areas, because of the island phenomenon they cause. However, the geological origins of mountains are multiple and they are located in different climatic regions. Nevertheless, in all aspects they reflect the basic elements of the local biologic unit. The shapes, climates, diverse water resources, biocenoses and the generated soils are the different components that determine, through their dynamic interaction, the “Mountain” ecosystem. Tectonic subduction processes lead to the development of islands such as Martinique, whose basic structure consists of a series of mountains (among them Mount Pele). Like the topographic divisions, the local micro-climates, water courses, different soils (themselves the consequences of the presence of the mountain itself) and successive volcanic eruptions determine, over time, the organization of the diverse vegetal entities.